The mechanisms of trust formation under different conditions of political identity: An experiment among Taiwanese voters. (October 2021) - Yang, Tien-Tun; Hsung, Ray-May; Chen, Shu-Heng; Du, Ye-Rong; Lin, Yi-Jr; Yen, Nai-Shing; Wu, Chien-Te; Liu, Ho-Ling
Trust and cooperation within and between political identity groups are important issues for building a healthy civil society and democratic development. However, this research problem has seldom been analyzed under different political identity conditions by means of experimental design in Taiwan. Presidential elections have reproduced the polarization between two groups of voters supporting different presidential candidates. Therefore, in this article the authors are interested in whether political identity matters in trust exchanges among strangers. This study applies a three-stage trust game experiment to examine how trust is developed within pairs of subjects with either the same or different political identity. In the first stage subjects were randomly matched in pairs as trustor and trustee, and their political identities were not disclosed. In the second stage the pairs were still randomly matched, but each subject was informed of their partner's political identity. In the final stage each subject could choose the preferred political identity of his/her partner. There were two mechanisms of trust-behavior formation under different identity conditions. The first mechanism was political identity. Supporters of presidential candidate Ma Ying-Jeou were more trustful than supporters of candidate Tsai Ing-Wen. Under the condition of subjects knowing their partner's political identity, the identity effect became strongly significant in stages 2 and 3 of the experiment, especially for that of the Ma–Ma group. The second mechanism was mutuality. The mutuality effect was very significant in all three stages of the trust experiment, and that effect was stronger for those who voted for Tsai.